RANCANGAN APLIKASI PEMINJAMAN PADA PERPUSTAKAAN BERBASIS DESKTOP DI UPTD SDN 3 RUKTI BASUKI - Chika Sari, Isda; Agus Priadi, Median (Jurnal Ilmiah Sistem Informasi (JISI), 2024)
UPTD Elementary School 3 Rukti Basuki was established in 1978, and school conditions have not changed from year to year, especially in the library section. With the research at Elementary School 3 Rukti Basuki, this research aims to create a desktop-based library information system application. This application seeks to maximize the function of information technology available in the library, facilitate data management into information in the form of reports, and reduce the use of paper (books), which are still used to record circulation in the library. Information technology in this library is essential because of the increased number of people working there. Implementing good information technology in the library will make information management easy and fast.